Desenvolvimento de procedimento para posicionamento e fixação de sistema de vibração unidirecional em chave seccionadora de alta tensão - Daronch, Juliano Wagner (2023)
When performing opening and closing maneuvers of high voltage disconnector switches, hot spots on the switch contacts can be observed when the maneuvers of this equipment occur inappropriately. To solve this problem, this work consists of developing a procedure to find the optimal fixing point of a vibration system in high voltage disconnector switches with vertical opening to aid in opening and closing maneuvers. The study is based on patent BR 10 2013020198 7, which proposes to use mechanical vibration to help increase the efficiency of the closing/opening process of disconnector switches together with the effective increase in operational safety, in order to increase efficiency in the operation of disconnector maneuvers. To develop the procedure, the vibration system was tested on a high-voltage disconnector switch with vertical opening, without the passage of electric current, installed at the UPFParque Technological Park, which is used on 230 kV lines. Accelerometers, LVDTs and other sensors were used to carry out experimental tests, where data were generated for the development of the procedure. Through experimental measurements, it was verified that the optimum point of fixing the motor vibrator, for the disconnector model tested, is close to the column of insulators that holds the fixed contact, with its vibration being in the direction of tightening the fixed contacts. Using the LVDT, it was possible to measure the times required for the correct closure of the contacts when exposed to forced harmonic vibration at different frequencies. With this data, the positioning and fixing procedure was developed, which was validated on a vertical opening high-voltage disconnector switch inside an electrical power substation. In this way, the use of unidirectional motor vibrators to aid maneuvers in disconnectors is an automation option for the electrical sector, and can be used in other disconnectors of the same construction format with their base being supported on metal structures.